Comparison of Nutritional Knowledge of Home Economics and Media Science students in Karachi - Sajjad, Sumaiya; Asar , Farzana (Nurture, 2015)
Nutritional knowledge is a prerequisite for making healthy food choices, however nutrition education is rarely provided at high school or undergraduate in Pakistan. Home Economics colleges are the only one that have been providing effective nutrition education since 1950s but this fact is not recognized and appreciated public or education department. The purpose of this study was to assess the impact of home economics education on the level of nutritional knowledge of Home Economics students by comparing them with Media Science students. Data was collected from a total of 200 students. A twenty item questionnaire was used to assess nutritional knowledge. Data analysis was done to assess and to compare nutritional knowledge on the basis of scoring which was categorized as (1-7= fair), (8-14= good) and (15-20=excellent). .A significantly higher proportion of Home economics students had excellent knowledge (90%) as compared to general science students (9%). The study identified significant differences in knowledge between both the departments. This is consistent with previous studies which showed that nutrition knowledge is related with the field of study.